Longitudinal analysis of injury risk in runners: Prevention strategies and treatment approaches - Roepajadi, Joesoef; turi, Moh; Ilmi, Mochamad Azhar; Bukry, Saiful Adli; Putri, Dinda Gamasista Intan Yuri (Edelweiss Applied Science and Technology, 2025)
Injuries to runners are an important issue in the world of sports, given the high number of incidents that impact performance and continuity of training. This study is motivated by the high prevalence of injuries, especially in the hamstring, knee, and ankle muscles, as well as the limited data-driven prevention approaches. The main objective of this study was to analyze injury risk factors longitudinally and evaluate the effectiveness of prevention strategies applied over one year. The study used a longitudinal panel design involving 60 runners aged 18–30 years. Data collection techniques included Oslo Sports Trauma Research Center questionnaires (OSTRC-Q), digital training logs, Visual Analogue Scale (VAS), Functional Movement Screen (FMS), and field observation for 12 months. Logistic regression analysis was used to determine the risk of injury. Results showed that weekly training load >80 km, injury history, BMI >25, and low adherence to prevention programs significantly increased the risk of injury (p<0.05). In conclusion, a prevention program that is consistently implemented can significantly reduce the risk of re-injury.